1998
DOI: 10.2307/3802343
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Age Determination Techniques for Gray Wolves

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Allen Press is collaborating with JSTOR to digitize, preserve and extend access to The Journal of Wildlife Management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
8

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(83 citation statements)
references
References 19 publications
1
72
0
8
Order By: Relevance
“…Unskinned body mass (BM) of skinned carcasses was estimated from their skinned body mass (SBM) using the regression BM = 0.97 SBM + 4.56 (r 2 = 0.91, n = 8 specimens for which both unskinned and skinned mass were known). The six live-captured animals were classed as more than 13 months old adult based on general tooth-wear patterns examined in the field (Bowen 1982;Landon et al 1998). Other specimens were aged by Matson's Laboratory, Inc., Milltown, Montana, using cementum layer analysis of a lower canine tooth (Linhart and Knowlton 1967;Landon et al 1998).…”
Section: Body and Skull Morphology Assessmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Unskinned body mass (BM) of skinned carcasses was estimated from their skinned body mass (SBM) using the regression BM = 0.97 SBM + 4.56 (r 2 = 0.91, n = 8 specimens for which both unskinned and skinned mass were known). The six live-captured animals were classed as more than 13 months old adult based on general tooth-wear patterns examined in the field (Bowen 1982;Landon et al 1998). Other specimens were aged by Matson's Laboratory, Inc., Milltown, Montana, using cementum layer analysis of a lower canine tooth (Linhart and Knowlton 1967;Landon et al 1998).…”
Section: Body and Skull Morphology Assessmentsmentioning
confidence: 99%
“…The six live-captured animals were classed as more than 13 months old adult based on general tooth-wear patterns examined in the field (Bowen 1982;Landon et al 1998). Other specimens were aged by Matson's Laboratory, Inc., Milltown, Montana, using cementum layer analysis of a lower canine tooth (Linhart and Knowlton 1967;Landon et al 1998). Specimens at least one year old were considered adults; however, the actual minimum age was approximately 20 months since specimens were killed after December.…”
Section: Body and Skull Morphology Assessmentsmentioning
confidence: 99%
“…Methods to age carnivores either rely on skull measurements or fusion of cranial sutures (Schweikher 1930;Smuts et al 1978;Gay and Best 1996), or analysis of dental characteristics, including tooth wear (e.g., Smuts et al 1978;Ashman et al 1983;Stander 1997), tooth color (Shaw 1986), tooth eruption (Linhart and Knowlton 1967;Smuts et al 1978;Van Horn et al 2003), cementum annuli (e.g., Laws 1952;Smuts et al 1978;Roulichová and Anděra 2007), width of the pulp chamber (e.g., Smuts et al 1978;Landon et al 1998), and gum-line recession (Currier 1979;Laundré et al 2000). However, the drawbacks of tooth wear and tooth color are that they might be dependent upon diet and degree of mastication (Currier 1979), and they are difficult to standardize and somewhat subjective (Linhart and Knowlton 1967;Laundré et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Estimating age with cementum annuli analysis may not be accurate for Wolves (Goodwin and Ballard 1985;Landon et al 1998). Gipson et al (2000) concluded that cementum annuli analysis underestimated actual age by 1-3 years for Wolves >3-14 years of age.…”
mentioning
confidence: 99%
“…(Young and Goldman 1944;Goodwin and Ballard 1985;Okarma and Koteja 1987;Mech 1988;Landon et al 1998;Mech and Boitani 2003). Mech (1988) stated that wild Wolves rarely exceed 13 years of age, and Peterson (1997:13) We document longevity and productivity of three Wolves (Canis lupus) in the wild in Montana and Idaho, USA.…”
mentioning
confidence: 99%